Re-Imagining Leadership Roles beyond the Shadow of Bureaucracy - Lisa Catherine Ehrich; Fenwick Walter English (MDPI AG, 2024)
The aim of this conceptual paper is to revisit the relationship between leadership and bureaucracy. The dominant and unquestioned way of thinking about leadership is to equate it as an undertaking exercised by leaders, those officers who occupy hierarchical positions in organizations. For example, senior leadership and middle leadership in schools are often associated with formal hierarchical roles played by senior and middle leaders. However, it can be argued that this perspective is problematic, not only because it is leader-centric but also due to its limitations in explaining the phenomenon of leadership. In order to understand the relationship between leadership and bureaucracy and leadership outside of bureaucracy, the paper reviews some of the extant literature in the field, including a brief history of bureaucracy, its pervasiveness in educational institutions, and current neo-liberal policies and reforms that function effectively within bureaucratic structures. An important contribution of the paper is a synoptic conceptual model that brings together three worldviews or archetypes pertaining to bureaucracy. These are a hard-edged view (system first, people second), a soft-edged view (people first, system second) and a third worldview (issue first, people second, system third). The third worldview signals a departure from the first two archetypes as it is an illustration of leadership outside the confines of bureaucracy.